Promoting Sustainable Sorghum Production: The Role of Ratoon Cultivation and Fertilizer Management - Mahpuzah, Marfiatun; Sopandie, Didy; Wirnas, Desta; Trikoesoemaningtyas (Journal of Tropical Crop Science, 2025)
This study investigated the biomass productivity of sorghum main crop, first ratoon, and second ratoon. A randomized complete block design was employed for the main crop experiment, with eight sorghum genotypes (NS2-19, NS2-102, NS2-109, NS2-111, NS2-140, IPB 4, IPB 8, and “Numbu”) as the treatment factor. The ratoon crop was designed using a Split Plots Design with two treatment factors and three replications. The first factor was fertilizer treatment on the ratoon crops, with two levels: complete N, P, and K fertilizer (urea 133 kg.ha-1, KCl 100 kg.ha-1, and SP-36 100 kg.ha-1) and N fertilizer only (urea 133 kg.ha-1); this factor was arranged as the main plot. The second factor comprised eight elite sorghum lines, the same as those used in the main crop experiment, arranged as subplots. The results indicated that complete NPK fertilization and N fertilizer alone produced similar biomass productivity in sorghum ratoon crops. Among the genotypes, NS2-140 demonstrated the highest biomass productivity in the main crop, NS2-109 in the first ratoon, and NS2-19 in the second ratoon. The second ratoon exhibited the highest biomass yield compared to the main crop and the first ratoon.